Fabrication of Gold Hyperdoped Silicon Photodetectors - Wu, Derrick (Université d'Ottawa | University of Ottawa, 2025)
Short wave infrared light has multiple applications across the fields of imaging, telecommunications, and defense. Photodetectors for use in this spectrum usually require expensive and rare materials such as InGaAs, Ge, or HgCdTe. By hyperdoping silicon with gold, the optical absorption cutoff wavelength can be extended from 1100 to 2500 nm, allowing silicon to replace these materials, leveraging the robustness, maturity, and know-how of the silicon microfabrication industry. This effect arises due the introduction of an intermediate band within silicon’s 1.12 eV bandgap. However, gold hyperdoped silicon is metastable, which must be considered to avoid gold segregation. A process flow for creating silicon-based short wave infrared photodetectors was designed and executed. Three device layouts were designed, named the Teeth, Corner, and Busbar design. The process flow was designed for industrial compatibility, avoiding the use of electron beam lithography and ion implantation of transition metals. Microfabrication work was done at the University of Ottawa’s NanoFab, except for ion implantation done commercially and pulsed laser mixing work done at Benet Laboratories in Watervliet, New York. External quantum efficiency and I-V measurements under 1310 nm laser illumination were performed on fabricated devices.
Keywords: Microfabrication; Short-Wave Infrared Photodetector; Gold Hyperdoping of Silicon